2018
DOI: 10.1002/tox.22542
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic potentials of salvianolic acid A on oral squamous cell carcinoma by targeting MMP‐2 and the c‐Raf/MEK/ERK pathway

Abstract: The metastasis of oral squamous cell carcinoma (OSCC) is one of the most important causes of cancer-related deaths. Thus, various therapeutic strategies have been developed to prevent the metastasis of OSCC. Salvianolic acid A (SAA), a traditional Chinese medicine, has antithrombosis, antiplatelet, anti-inflammation, and antitumor activities. Here, we provide molecular evidence indicating that SAA exerts its antimetastatic effects by markedly inhibiting the invasion and migration of oral squamous SCC-9 and SCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
2
16
1
Order By: Relevance
“…Previous studies have shown that blocking the MAPK/ERK signaling cascade can inhibit MMP2 expression and inhibit the metastasis of oral squamous cell carcinoma. 36 Our results showed that oxymatrine not only reduced expression levels of RAS, p-RAF, p-MEK, and p-ERK, but also those of C-MYC and MMP2, similar to the effects of salirasib. Inhibition of upstream protein expression can reduce expression of downstream proteins in the same signaling pathway.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have shown that blocking the MAPK/ERK signaling cascade can inhibit MMP2 expression and inhibit the metastasis of oral squamous cell carcinoma. 36 Our results showed that oxymatrine not only reduced expression levels of RAS, p-RAF, p-MEK, and p-ERK, but also those of C-MYC and MMP2, similar to the effects of salirasib. Inhibition of upstream protein expression can reduce expression of downstream proteins in the same signaling pathway.…”
Section: Discussionsupporting
confidence: 70%
“…Despite efforts to improve its early diagnosis and treatment, advanced OSCC still has an extremely poor 5-year survival rate of less than 63%, mainly due to high recurrence rates brought about by its ability to invade local tissues and to metastasize [4]. Surgery remains the first-line treatment for a significant proportion of patients with OSCC [5].…”
Section: Introductionmentioning
confidence: 99%
“…In cardiac fibrosis, danshensu has been found to inhibit β-adrenergic receptor-mediated fibroblast proliferation and collagen-I synthesis primarily by suppressing p38 signaling pathway (28). Recently, one study has shown than salvianolic acid A can prevent OSCC metastasis by inhibiting Raf/MEK/ERK signaling pathway, which subsequently causes reduction of MMP-2 expression (29). To investigate the molecular mechanism involved in sodium danshensu-mediated anti-metastatic effects, we thought of examining the level and activity of conventional MAPKs, including ERK1/2, JNK1/2, and p38.…”
Section: Discussionmentioning
confidence: 99%